2018
DOI: 10.1016/j.system.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

L1 – L2 semantic and syntactic processing: The influence of language proximity

Abstract: This study examined the extent to which a first language (L1) influences a second language (L2). We explored this potential influence by evaluating participant responses for semantic and syntactic word strings composed from the 1K British National Corpora word list. We investigated two different first language groups, and assessed their responses to semantic and syntactic judgement tasks in their L2 (English), alongside an English control group. The participants were L1 Japanese (n = 23), L1 Italic Indo-Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…These findings may have some parallels with those of Booth, Clenton and Van Herwegen (2018), with regard to word order processing in a second language. Booth et al (2018) gave syntactic and semantic tasks involving English word strings to individuals who were learning English as a second language.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These findings may have some parallels with those of Booth, Clenton and Van Herwegen (2018), with regard to word order processing in a second language. Booth et al (2018) gave syntactic and semantic tasks involving English word strings to individuals who were learning English as a second language.…”
Section: Discussionsupporting
confidence: 61%
“…These findings may have some parallels with those of Booth, Clenton and Van Herwegen (2018), with regard to word order processing in a second language. Booth et al (2018) gave syntactic and semantic tasks involving English word strings to individuals who were learning English as a second language. One group came from Italic Indo-European language first language backgrounds (French, Spanish, Portuguese, Italian and Romanian) whose default word order is subject-verb-object, as is the case for English.…”
Section: Discussionsupporting
confidence: 61%
“…It has also been argued that the expert intuitions on which syntactic theory is based are fl awed due to confi rmation bias (syntacticians presumably want the data to support their theory) (Dąbrowska 2010). It could also be that such intuitions are affected by knowledge of other languages (due to mere exposure to foreign languages or outright bilingualism) (Bohnacker 2006;Booth, Clenton & Van Herwegen 2018). In short, the question is whether we can be confi dent that there is an underlying universal constraint that results in the grammaticality judgements in (1), and if not, what about locality?…”
Section: Introduction: the Standard Patternmentioning
confidence: 99%
“…Yet there appears to be a gap in the research concerning how and why Qallunaat learn Inuktitut. This is an important distinction to explore, since a LL's L1 has an effect on how easily they can learn an L2 from a different language family (Booth, Clenton & Van Herwegen, 2018). Almost no…”
Section: Second Language Acquisitionmentioning
confidence: 99%
“…Resources. Yet the disparity between L1 and L2 do seem to be an issue as well: Studies such as Booth, Clenton and Van Herwegen (2018) have shown that LLs with a large distance between L1 and L2 have a more difficult time learning semantics (the meaning of words) in their L2 compared to LLs with a small distance. However, both groups of learners (those with large and small distances between L1 and L2) learn other aspects of the L2 equally well (or poorly), such as the syntax.…”
Section: Difficulties Learning Inuktitutmentioning
confidence: 99%